PENGARUH WAKTU PEMERAMAN TERHADAP KEKUATAN PAVING BLOCK PASCA PEMBAKARAN MENGGUNAKAN MATERIAL TANAH DAN KAPUR UNTUK JALAN LINGKUNGAN - Andius Dasa Putra; Setyanto Setyanto; Onika Permata Sari (UNIVERSITAS LAMPUNG, 2014)
Infrastructure rapid development sometimes had negative impact, such as the use of impermeable pavement layers which result the infiltration be hampered. By utilizing the paving block, it can resolve o f infrastuture development problem. Known, paving block is composition of building materials that made from the mixture of portland cement or hydraulic adhesives, water, and agrregates with or without the other ingridient as defined in SNI 03-0691-19996. To find the other alternatives then will do the assesment with the limestone and soil. Soil samples were tested from Desa Karang Anyar, South Lampung. The composition of mixture was used 6 %, 8 % and 10 %, with curing time during 7, 14 and 28 days, and the treatment with or without combustion and then paving block were tested with compressive strength and water absorption. The research results obtained by the characteristics of the soil is a clay samples. The average value of compressive strength was linearly proportional to the amount of lime composition. The compressive strength during 28 days of curring time and without combustion was from 32,96 kg/cm2 to 10,87 kg/cm2, then the compressive strength with combustion was from 16,99 kg/cm2 to 56,91 kg/cm. Water absorption test value was inversely proportional to the amount of lime composition. The water absorption was from 10,07% to 15,07%. The compressive strength resulting over all still not include the specifications of paving block in SK - SNI 03-1996, also for the compressive strength was 85 kg/cm2. The value of water absorption test were not include the specifications of paving block SK SNI - 03 - 0691-1996 which ranges from 3 % - 10 %.